Improving Your Splunk Skills Leverage the operational intelligence capabilities of Splunk to unlock new hidden business insights - D. Miller, James (Packt Publishing Limited, 2019)
bTransform machine-generated data into valuable business insights using the powers of Splunk/b h4Key Features/h4 ulliExplore the all-new machine learning toolkit in Splunk 7.x /li liTackle any problems related to searching and analyzing your data with Splunk /li liGet the latest information and business insights on Splunk 7.x/li/ul h4Book Description/h4 Splunk makes it easy for you to take control of your data and drive your business with the cutting edge of operational intelligence and business analytics. Through this Learning Path, you'll implement new services and utilize them to quickly and efficiently process machine-generated big data. You'll begin with an introduction to the new features, improvements, and offerings of Splunk 7. You'll learn to efficiently use wildcards and modify your search to make it faster. You'll learn how to enhance your applications by using XML dashboards and configuring and extending Splunk.
Keywords: COMPUTERS / Enterprise Applications / Business Intelligence Tools; COMPUTERS / System Administration / General